IN VITRO ANTIBACTERIAL ACTIVITY OF NEEM LEAVES ON EXTENDED-SPECTRUM BETA-LACTAMASE AND AMBLER CLASS C COPRODUCERS FROM SKIN AND SOFT-TISSUE INFECTIONS. - Shah, Pratibha J; Williamson, Manita T (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Clinical isolates coproducing extended-spectrum beta-lactamase (ESBL) and Ambler Class C (AmpC) beta-lactamase are a therapeutic challenge. The aim of the present study was to evaluate the antibacterial activity of Azadirachta indica methanolic leaf extract against lactose fermenting coproducers of ESBL and AmpC isolated from skin and soft-tissue infections (SSTIs). Methods: A total of 88 non-duplicate lactose fermenting strains isolated from SSTIs specimens were tested for their antibiotic susceptibility pattern by Kirby-Bauer disk diffusion method. Ceftazidime and cefoxitin-resistant strains were screened for coproduction of ESBL and AmpC beta-lactamase by phenotypic confirmatory disc diffusion test and E-test. Antibacterial activity of methanolic neem leaf (NLM) extract was examined by the disc diffusion method and the minimum inhibitory concentration (MIC) of NLM was determined by the agar dilution technique. Results: Thirty-seven lactose fermenting strains were confirmed to be coproducers of ESBL and AmpC, out of which 27 were Escherichia coli and 10 were Klebsiella spp. The nimbin content in the neem leaf extract was found to be 0.007% (w/w) by high-performance liquid chromatography (HPLC) analysis. The NLM extract showed inhibitory activity against all the 37 lactose fermenting isolates from SSTIs, coproducing ESBL and AmpC. The MIC of NLM extract was determined to be in the range of 4–8% (40–80 mg/ml) against the selected isolates. Conclusion: It can be stated that NLM extract might have therapeutic significance against coproducers of ESBL and AmpC beta-lactamase isolated from SSTIs.